Guia de possibilidades para o uso da música no ensino de História: a relação interdisciplinar entre música e história a partir das dissertações do Profhistória - Santos, Wesley Herculano dos (2022)
This work presents a discussion about the use of music in the teaching of history, with emphasis on the possibilities found in ProfHistória's dissertations. To this end, it was first necessary to work on concepts related to history and music, as well as with some possibilities of association between the two areas, with an emphasis on the use of music in the teaching of history. Occupies an importance There is space in the text for the presentation of some authors interested in the research on the history of music in Brazil. From there, the possibilities of interactions between music and history in the school environment are verified from the exhibition of works with this theme, especially within the dissertations prepared for ProfHistória. In these works, we observe that music, in most cases, is used as an object of study, or even as a source for history. In addition, the work of this dissertation presents a Guide of possibilities for the use of music in the teaching of history, in order to contribute mainly to teachers who do not fully master the musical language. In this guide, some concepts necessary for understanding the proposed tool are presented. It exposes the possibilities of uses of music in the teaching of history found in the researched dissertations and other proposals related to the theme.